'Within my work environment I don't see gender as an issue': Reflections on gender from a study of criminal justice social workers in Scotland. (March 2021) - McCulloch, Trish; Cree, Viviene E; Kirkwood, Steve; Mullins, Eve
Community justice professionals operate within deeply gendered territory, yet there has been little attention to how gender is understood and embodied by the workforce. Building on findings from a mixed method study, this article explores professional perceptions of how gender plays out in criminal justice social work (CJSW) in Scotland. Our findings demonstrate that gender is an important but neglected dimension of CJSW. We conclude that advancing gender in this field requires a more inclusive theorising of gender in professional education and research, a more practical commitment to gender equality in policy and practice, and more routine opportunities for dialogue on issues of gender and justice within and across these domains.